2020
DOI: 10.4067/s0718-58392020000100050
|View full text |Cite
|
Sign up to set email alerts
|

Integrated effects of herbicides and foliar fertilizer on corn inbred line

Abstract: Plant response to herbicides is one of the most essential points in corn (Zea mays L.) production, especially in inbred lines. Weed abundance is higher in corn lines comparing to hybrids. Insufficient herbicide selectivity in lines crop can be a limiting factor for their application. Weed control today is based on Integrated Weed Management (IWM) approach, i.e. to use all possible methods and measures for weed control and better crop fitness. In this research, sensitivity of one corn inbred line (selection bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Banothu and Uma (2021) showed that stress conditions are associated with changes in various phenolic compounds. In the work of Brankov et al (2020), the content of phenolic, proteins, total carotenoid content, total chlorophyll, and Pphy, was diverse in maize leaves treated with different herbicide doses. Foster and Brust (1995) noticed that the insecticide carbofuran may be acting as a growth stimu-lant, as well as an insecticide on watermelon.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Banothu and Uma (2021) showed that stress conditions are associated with changes in various phenolic compounds. In the work of Brankov et al (2020), the content of phenolic, proteins, total carotenoid content, total chlorophyll, and Pphy, was diverse in maize leaves treated with different herbicide doses. Foster and Brust (1995) noticed that the insecticide carbofuran may be acting as a growth stimu-lant, as well as an insecticide on watermelon.…”
Section: Resultsmentioning
confidence: 99%
“…Also, to explore and identify low phytic acid genotypes diverse sets of maize landraces, inbred lines, and hybrids were analyzed for phytic acid content (Drinić Mladenović et al, 2009;Dragičević et al, 2013;Yathish et al, 2021;Kahriman et al, 2021). Brankov et al (2020) tested herbicides and foliar fertilizer mixtures on grain composition in maize inbred lines and found a significant environmental impact on phytic acid content in maize.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, soil deficiency in micro-elements can be successfully managed by foliar fertilizing and must be the preferred way to apply microelements (Tejada et al, 2018). In some cases, fertilizers and herbicides can be combined in order to help crops to overcome possible herbicide stress (Brankov et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Maize (Zea mays L.) is the most important cereal crop worldwide [1], with an average harvested area of 198,869,908.20 ha and production of 1,154,945,359.65 t from 2017 to 2021 [2]. In the Republic of Serbia, maize is the most important arable crop [3] and provides staple food to a large portion of the human population [4]. As a cereal, maize dominates, comprising 53.0% of the harvested area.…”
Section: Introductionmentioning
confidence: 99%